EEG Alpha Desynchronization in Musicians and Nonmusicians in Response to Changes in Melody, Tempo, and Key in Classical Music. - Overman, Amy A.; Hoge, Jessica; Dale, J. Alexander (Perceptual & Motor Skills, 2003)
Two experiments were performed to examine musicians' and nonmusicians' electroencephalographic (EEG) responses to changes in major dimensions (tempo, melody, and key) of classical music. In Exp. 1, 12 nonmusicians' and 12 musicians' EEGs during melody and tempo changes in classical music showed more alpha desynchronization in the left hemisphere (F3) for changes in tempo than in the right. For melody, the nonmusicians were more right-sided (F4) than left in activation, and musicians showed no left-right differences. In Exp. 2, 18 musicians' and 18 nonmusicians' EEG after a key change in classical music showed that distant key changes elicited more right frontal (F4) alpha desynchronization than left. Musicians showed more reaction to key changes than nonmusicians and instructions to attend to key changes had no significant effect. Classical music, given its well-defined structure, offers a unique set of stimuli to study the brain. Results support the concept of hierarchical modularity in music processing that may be automatic. Reprinted by permission of the publisher.